항우울제 중단 증후군 - 김세현; 김용식; 강웅구 (Singyŏng chŏngsin ŭihak, 2024)
Since selective serotonin reuptake inhibitors were introduced in clinical practice in the 1990s, antidepressant prescriptions have steadily increased. In addition to the prescriptions by psychiatrists, antidepressant prescriptions by non-specialists have also increased. An advanced understanding of the pharmacological and clinical characteristics of antidepressants is essential to improving the treatment response of depressive disorders and the quality of life of patients. Antidepressant withdrawal or discontinuation syndrome can frequently occur if antidepressant maintenance is discontinued without a pre-planned clinical strategy. Nevertheless, it is often unrecognized or mistaken for other clinical situations. This causes patient distress and ultimately reduces long-term treatment compliance. Inappropriate therapeutic decisions can be made if clinicians do not recognize antidepressant discontinuation syndrome. Antidepressant withdrawal is common and preventable. This issue must be recognized because it can be adjusted through appropriate clinical management. This article systematically reviews the clinical features, biological mechanisms, coping strategies, and antidepressant discontinuation strategies related to antidepressant discontinuation syndrome. KCI Citation Count: 0